Menanamkan pendidikan karakter oleh keluarga sebagai pendidik pertama - Mawardi, Nadya Mustaqhfiroh (Maliki Interdisciplinary Journal, 2026)
Early childhood refers to individuals between the ages of 0-6 years old who experience rapid growth and development. Therefore, it is during this period that they receive appropriate stimulation from their surroundings. The family is the primary and first environment that shapes a child's character, leading to noble character, through role models, communication, and positive habits. A safe, comfortable, and loving family environment can support the development of every aspect of a child. Challenges faced by parents in this digital age include excessive gadget use and a lack of direct interaction between parents and children, necessitating guidance and supervision involving active communication. Authoritative parenting styles, the provision of rewards and sanctions, and collaboration with the school can also be solutions that parents can implement. Thus, character formation in children can benefit emotional development, discipline, and interaction skills in the future. It can be concluded that a child's character is determined by the quality of interaction and care provided by the family, as well as the success in creating a safe, comfortable, and loving environment.